Soil phosphorus crisis in the Tibetan alpine permafrost region - Jiangtao Hong; Bo Pang; Lirong Zhao; Shumiao Shu; Puyu Feng; Fang Liu; Ziyin Du; Xiaodan Wang (Nature Communications)
Abstract Phosphorus (P) is an essential nutrient for living systems and is critical to the functioning of ecosystems. Permafrost areas have a huge reservoir of soil P that is currently not used very much; however, the direction and magnitude of changes in soil P stocks across the Tibetan alpine permafrost regions over recent decades remain unclear and the P budget has not been well assessed. Here we use a unique combination of a soil resampling method and a modified process-balanced model to assess the historical dynamics of soil P pools (0–30 cm depth) and the key flows of P in ecosystems across Tibetan alpine permafrost region. Compared with the 1980s, the soil P stock decreases dramatically by 36.1% in the 2020 s, decreasing from 346.5 to 221.4 Tg P (1 Tg = 1012 g) during the last three decades. Water erosion accounts for 82.3% of the total soil P outflow. Our projections suggest that the soil P stock will only be 20.3% of the 1980s stock by the end of this century, leading to an unprecedented crisis of P limitation in permafrost regions.